Tradisi Te'nea dalam Perspektif Hukum Islam (Studi Kasus di Desa Majannang) - Hendra Wijaya; Akbar, Fadlan (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2020)
The purpose of this research was to identify the description of te'nea tradition, to recognize the driving force behind the shift in the meaning of te’nea tradition, and to explain the view of Islamic law regarding te’nea tradition in Majannang Village, Parigi District, Gowa Regency. The research method employed field research studies with a case study format through sociological and normative approaches.. The results showed that te'nea tradition was initially conducted merely with the purpose of kinship and eating together with relatives in an effort to commemorate the ancestors of the Pajaiyya extended family. The shift of the meaning of te'nea tradition occurred due to healing phenomenon of a broken leg sufferer in Bungung Toa where the ritual of te'nea took place. The shift of the tradition of te'nea is very fatal because it is suspected to contain shirk which has implications for the haram of this tradition in the perspective of Islamic Law, but if the element of shirk can be eliminated then this tradition will be in line with the teachings of friendship which is mustahab (recommended).